Ibuprofen Solid Oral Dosage Composition Comprising a Methacrylic Acid Copolymer (2013)
Aspects of the invention include organoleptically acceptable solid oral dosage compositions of ibuprofen. Solid oral dosage compositions according to certain embodiments include ibuprofen and a methacrylic acid copolymer in an amount sufficient to make the composition organoleptically acceptable for administering in an oral cavity of a subject to deliver ibuprofen to the subject. Methods for preparing and using solid oral dosage compositions of the invention are also described.